The significance of the successors (Al-tābiūn) In the early hadīth collections - (:unkn) unknown (Bursa IlahIyat Vakfi, 2013)
In the early generations of Islam, the Successors (al-tābiūn) played an important role by making significant contribution to the formation of Islamic sciences such as fiqh, hadīth, and tafsīr. Thus, it is not surprising to see various references to their opinions in the early examples of different Islamic literary genres. For example, early hadīth collections include a great number of traditions attributed to the Successors - which would later be called al-hadīth al-maqū'-alongside those attributed to the Prophet. This paper, focusing on the usages of al-hadīthh al-maqū' in the early literature, is an inquiry into why the Successors' opinions constituted such an important part of hadīth collections. It argues that the veneration of the Successors is derived from the common recognition that they were better qualified to understand religious texts than later generations and that even their personal opinions were either based on the religious texts or at least consistent with them. The historical basis of this widely accepted recognition is the existence of an intimate and close teacher-student relationship between the Companions and the Successors, which made it possible for the latter to inherit the knowledge of the former. © Bursa I˙lahiyat Foundation.
Keywords: al-tābi'ūn; Hadīth; Maqtū hadīth; Sunna; The successors